Evaluation of antimicrobial photodynamic therapy against Streptococcus mutans biofilm in situ - Panhóca, V. H.; Florez, F. L.E. [UNESP]; de Faria, N. Batista [UNESP]; Rastelli, Alessandra Nara de Souza [UNESP]; Tanomaru, J. M.G. [UNESP]; Kurachi, C.; Bagnato, V. S. (Jaypee Brothers Medical Publishing, 2016)
Aim: This study investigated the effect of antimicrobial photodynamic therapy (aPDT) over Streptococcus mutans biofilm. Materials and methods: Eighteen (n = 18) patients were selected and one palatine device with dental blocks was used. The biofilm was treated by curcumin and Photogem® with a LED and the effect was analyzed by CFU/ml. Results: Although, statistical analysis showed significant reductions for aPDT mainly with Photogem® (p = 0.02), these were low. Conclusion: The results suggest a low antimicrobial effect of aPDT over S. mutans biofilm. Some parameters used need to be improved. Clinical Significance: This technique can be a promising in Dentistry.
Keywords: Biofilm; Curcumin; Dental caries; Photodynamic therapy; Randomized clinical trial; Streptococcus mutans